Intracerebroventricular MOTS-C Infusion Suppresses Thyroid Hormone Secretion in Rats - Bahar, Mehmet Refik; Tekin, Suat; Beytur, Asiye; Ozyalm, Fatma; Onalan, Ebru Etem; Sandal, Suleyman (Wiley, 2019)
[Abstract Not Available]
Keywords: MOTS-c; TRH; TSH; T3; T4